Im having trouble with this problem here:

x-->0 tan6x / sin2x

So far I only have:

(sin6x / cos6x) / (2sinx cosx)

What would be the next step? Multiply the reciprocal?

Also, could somebody tell me if Im doing this problem right?

x--> 0 (sin (cosx)) / secx

sin (cosx) / 1/cosx

sin (cosx) cosx

sin (1) 1 = sin 1

x-->0 tan6x / sin2x

So far I only have:

(sin6x / cos6x) / (2sinx cosx)

What would be the next step? Multiply the reciprocal?

Also, could somebody tell me if Im doing this problem right?

x--> 0 (sin (cosx)) / secx

sin (cosx) / 1/cosx

sin (cosx) cosx

sin (1) 1 = sin 1

Last edited: